RIP1 kinase activity promotes steatohepatitis through mediating cell death and inflammation in macrophages - Tao, Liang (Cell Death Differ, 2020)
Hepatocyte cell death and liver inflammation have been well recognized as central characteristics of nonalcoholic steatohepatitis (NASH), however, the underlying molecular basis remains elusive. The kinase receptor-interacting protein 1 (RIP1) is a multitasking molecule with distinct functions in regulating apoptosis, necroptosis, and inflammation. Dissecting the role of RIP1 distinct functions in different pathophysiology has absorbed huge research enthusiasm. Wild-type and RIP1 kinase-dead (Rip1(K45A/K45A)) mice were fed with high-fat diet (HFD) to investigate the role of RIP1 kinase activity in the pathogenesis of NASH. Rip1(K45A/K45A) mice exhibited significantly alleviated NASH phenotype of hepatic steatosis, liver damage, fibrosis as well as reduced hepatic cell death and inflammation compared to WT mice. Our results also indicated that both in vivo lipotoxicity and in vitro saturated fatty acids (palmitic acid) treatment were able to induce the kinase activation of RIP1 in liver macrophages. RIP1 kinase was required for mediating inflammasome activation, apoptotic and necrotic cell death induced by palmitic acid in both bone marrow-derived macrophage and mouse primary Kupffer cells. Results from chimeric mice established through lethal irradiation and bone marrow transplantation further confirmed that the RIP1 kinase in hematopoietic-derived macrophages contributed mostly to the disease progression in NASH. Consistent with murine models, we also found that RIP1 kinase was markedly activated in human NASH, and the kinase activation mainly occurred in liver macrophages as indicated by immunofluorescence double staining. In summary, our study indicated that RIP1 kinase was phosphorylated and activated mainly in liver macrophages in both experimental and clinical NASH. We provided direct genetic evidence that the kinase activity of RIP1 especially in hematopoietic-derived macrophages contributes to the pathogenesis of NASH, through mediating inflammasome activation and cell death induction. Macrophage RIP1 kinase represents a specific and potential therapeutic target for NASH.